2013
DOI: 10.1088/0256-307x/30/12/121101
|View full text |Cite
|
Sign up to set email alerts
|

Holographic Superconductor Models with RF 2 Corrections

Abstract: We investigate the effect of the RF 2 correction on the holographic superconductor model in the background of AdS black hole. We find that, similar to the effect caused by the Weyl correction, the higher RF 2 correction term can make it easier for the scalar operator to condense and result in the larger deviations from the expected relation in the gap frequency. However, if a non-trivial hair for the black hole has been triggered, we observe that the RF 2 correction and the Weyl correction do play different ro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 46 publications
(66 reference statements)
3
10
0
Order By: Relevance
“…As another example, we set u m = 9/10 which can relax the breakdown when the matching point approaches the allowable region. The right graph of Fig.2 proves this point and shows that the critical magnetic field B c 2 decreases as we amplify z which is qualitatively in good agreement with the work of [42]. When T ∼ T c we can have B c 2 ∝ (1 − T /T c ) for different Lifshitz scaling which agrees well with the Ginzburg-Landau theory.…”
Section: B the Upper Critical Magnetic Fieldsupporting
confidence: 85%
See 3 more Smart Citations
“…As another example, we set u m = 9/10 which can relax the breakdown when the matching point approaches the allowable region. The right graph of Fig.2 proves this point and shows that the critical magnetic field B c 2 decreases as we amplify z which is qualitatively in good agreement with the work of [42]. When T ∼ T c we can have B c 2 ∝ (1 − T /T c ) for different Lifshitz scaling which agrees well with the Ginzburg-Landau theory.…”
Section: B the Upper Critical Magnetic Fieldsupporting
confidence: 85%
“…It is observed that corresponding to the lower critical temperature, the gap becomes increasingly smaller as z increases than the results in [42].…”
Section: The D-wave Holographic Superconductor Models With Lif-shmentioning
confidence: 63%
See 2 more Smart Citations
“…Another special combination of these non-minimal terms may be obtained from a five dimensional Gauss-Bonnet gravity via dimensional reduction [10]. Holographic properties of the later non-minimal model are investigated in Schwarzschild-AdS [11] and in the charged black hole background [12].…”
Section: Introductionmentioning
confidence: 99%